Ethnic and Confessional Relations in Cross-Border Regions: A Comparative Analysis Based on Sociological Research - Lopatynskyi, Yurii; Balukh, Vasil (George Fox University, 2020)
The study deals with the issues of confessional issues (religiosity), freedom of conscience, state-church relations, interethnic relations, cultural identity, and language use in cross-border regions of Ukraine. The purpose of the article is to find common features in the relations between different nationalities and representatives of the multi-confessional environment of the two cross-border regions of Ukraine and to identify the specifics of each of them in solving the most important life problems of inter-ethnic and inter-confessional relations. The method of sociological research is a survey that contains 44 questions of mixed type. The research was carried out by the Center for Sociological Research of Yuriy Fedkovych Chernivtsi National University. The principle of research is random selection of respondents according to social-age groups. About 1,500 respondents were interviewed. The data analysis method is SPSS electronic system (Statistical Package for the Social Science). The results of the comparative analysis were obtained.
-
Keywords: ethno-confessional relations; cross-border regions; sociological research; Ukraine